Primer registro de coyote (Canis latrans) en la región de la Selva Lacandona, Chiapas, México - Peña-Mondragón, Juan; Castillo Álvarez, Alicia; Benítez Malvido, Julieta (Instituto de Ecología, A.C., 2014)
Using photo trapping we obtained the first record of coyote in the Lacandon area, Chiapas, confirming the presence of this predator in the region. We relate the presence of this predator to livestock predation.